Measurement, Control, and Communication Using IEEE 1588 - Eidson, John C. (Advances in Industrial Control, 2006)
A common sense of time among all the elements of a distributed measurement and control system allows the use of new techniques for the solution of problems with complex synchronization requirements or arising from the interaction of many sensors and actuators. Such a common sense of time may be accomplished using IEEE Standard for a Precision Clock Synchronization Protocol for Networked Measurement and Control Systems (IEEE 1588-2002) to synchronize real-time clocks incorporated within each component of the system. IEEE 1588, published in November 2002, is a technology new to the engineering community expanding the performance capabilities of Ethernet networks so that they become relevant for measurement and control; this monograph embodies the first unified treatment of the associated technology, standards and applications. Readers unfamiliar with IEEE 1588 will gain understanding of the context of the technology it represents and, from three chapters of case studies, its role in a variety of application settings. To engineers implementing synchronization within their systems Measurement, Control, and Communication Using IEEE 1588 provides detailed discussion of the complex features of the standard. Together with the essential material on best practice and critical implementation issues, these provide invaluable assistance in the design of new applications. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.